Corrosion of CO2 transport and injection pipeline steels due to the condensation effects caused by SO2 and NO2 impurities. Issue 4 (17th December 2013) - Yevtushenko, O.; Bettge, D.; Bäßler, R.; Bohraus, S.
<x xml:space="preserve">Abstract</x> Condensates from the gas stream in simulated CO2 transport pipelines have been identified during the experiments in the laboratory. Because of their acidic origin the corrosion resistance of pipeline steels used for CCS (carbon capture and storage) technology might be limited. Over the last years it has become clear that the amount of water and acid building constituents in the CO2 stream has to be controlled very well. In this work, condensates formed in experiments using gaseous CO2 containing high amounts of water, NO2 and SO2 were analyzed, replicated, and used for extensive electrochemical experiments. These highly acidic condensates were enriched with CO2 and then applied to characteristic steels planned to use in the CCS transport chain. Even high alloy steels are susceptible to localized corrosion under these conditions. The results implicate that condensation of aggressive acid droplets has to be avoided or the locations where condensation takes place have to be controlled extensively.